2019
DOI: 10.1111/ina.12557
|View full text |Cite
|
Sign up to set email alerts
|

Airborne transmission between room occupants during short‐term events: Measurement and evaluation

Abstract: This study experimentally examines and compares the dynamics and short‐term events of airborne cross‐infection in a full‐scale room ventilated by stratum, mixing and displacement air distributions. Two breathing thermal manikins were employed to simulate a standing infected person and a standing exposed person. Four influential factors were examined, including separation distance between manikins, air change per hour, positioning of the two manikinsand air distribution. Tracer gas technique was used to simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 38 publications
(109 reference statements)
3
55
0
Order By: Relevance
“…In earlier studies, pathogen transmission has been investigated widely in various indoor environments ( Li et al, 2007 , Morawska et al, 2017 , Ai and Melikov, 2018 ). In many cases, CFD and experimental studies have been conducted to examine the airborne transmission in simplified environments ( Yu et al, 2004 , Zhang and Chen, 2006 , Liu et al, 2017 ) that may have an association with ventilation ( Li et al, 2005 , Olmedo et al, 2012 , Cao et al, 2015 ), airflow interaction ( Bivolarova et al, 2017 , Li et al, 2018a , Ai et al, 2019 ), in hospitals ( Yu et al, 2005 , King et al, 2015 , Cho, 2019 ) and offices ( He et al, 2011 ). Certain studies also consider transport induced by human motion ( Edge et al, 2005 , Han et al, 2014 ) as well as breathing, talking and coughing ( Gupta et al, 2010 , Licina et al, 2015 , Li et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies, pathogen transmission has been investigated widely in various indoor environments ( Li et al, 2007 , Morawska et al, 2017 , Ai and Melikov, 2018 ). In many cases, CFD and experimental studies have been conducted to examine the airborne transmission in simplified environments ( Yu et al, 2004 , Zhang and Chen, 2006 , Liu et al, 2017 ) that may have an association with ventilation ( Li et al, 2005 , Olmedo et al, 2012 , Cao et al, 2015 ), airflow interaction ( Bivolarova et al, 2017 , Li et al, 2018a , Ai et al, 2019 ), in hospitals ( Yu et al, 2005 , King et al, 2015 , Cho, 2019 ) and offices ( He et al, 2011 ). Certain studies also consider transport induced by human motion ( Edge et al, 2005 , Han et al, 2014 ) as well as breathing, talking and coughing ( Gupta et al, 2010 , Licina et al, 2015 , Li et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…The airborne transmission of a virus and the consequent contagion risk assessment is a complex issue that requires multidisciplinary knowledge. It is necessary to understand the characteristics and mechanisms behind the generation of respiratory microdroplets ( Ai and Melikov, 2018 , Holmgren et al, 2010 ), the survival of viruses in microdroplets ( van Doremalen et al, 2020 ), the transport of microdroplets and human exposure to them ( Ai et al, 2019a ), and the airflow patterns that carry microdroplets in buildings ( Ai et al, 2019b ). Expiratory human activities generate virus-carrying microdroplets that are small enough to remain aloft in air during exhalation, talking, and coughing ( Holmgren et al, 2010 , Morawska et al, 2009 , Morawska and Cao, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nosocomial infections (NIs), also known as hospital-acquired infections, are mainly caused by airborne pathogens and interpersonal contact in hospitals. It has been reported that the air in hospitals and other health service buildings contains microbial aerosols, and thus controlling the level of pathogenic microbial infections ensures the safety of workers and patient groups (Ai et al 2019;Lanzerstorfer et al 2019). Studies have confirmed that viruses also exist in the air and are very likely to spread via airborne transmission (Guo et al 2020;Ong et al 2020).…”
Section: Introductionmentioning
confidence: 99%